Preparation of Listerin antigen as a tool for Diagnosis of listeriosis - Al - Khatib, G. M.; Al - Haddad, Zainab A.A.; Al- Hissen, Sanaria Fawzi; Al- Kutbi, Sahar Hassan (The Iraqi Journal of Veterinary Medicine, 2004)
This study was conducted to produce a specific antigen for detection L. monocytogenes infection. The antigen was prepared by culturing L. monocytogenes on suitable media and then disrupted by ultrasonicatorwaves. The water – soluble extract of sonically disrupted Listeria were used for skin testing guinea pigs infected with (1*108 CFU / ml) of a L. monocytogenes. Two infected doses were used for immunization at intervals of (10) days between them. Two skin tests were done, 10 days and 15 days after the 2nd infected dose. The skin test results were read after 24 & 48 hrs. which showed clear thickening differences and redness at the injection sites after 24 hrs. and become more clear after 48 hrs.